Bulk binding approach for PMIPv6 protocol to reduce handoff latency in IoT - Adnan J. Jabir (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Mobility management protocols are very essential in the new research area of Internet of Things (IoT) as the static attributes of nodes are no longer dominant in the current environment. Proxy MIPv6 (PMIPv6) protocol is a network-based mobility management protocol, where the mobility process is relied on the network entities, named, Mobile Access Gateways (MAGs) and Local Mobility Anchor (LMA). PMIPv6 is considered as the most suitable mobility protocol for WSN as it relieves the sensor nodes from participating in the mobility signaling. However, in PMIPv6, a separate signaling is required for each mobile node (MN) registration, which may increase the network signaling overhead and lead to increase the total handoff latency. The bulk binding approaches were used to enhance the mobility signaling for MNs which are moving together from one MAG to another by exchanging a single bulk binding update message. However, in some cases there might be several MNs move at the same time but among different MAGs. In this paper, a bulk registration scheme based on the clustered sensor PMIPv6 architecture is proposed to reduce the mobility signaling cost by creating a single bulk message for all MNs attached to the cluster. Our mathematical results show that the proposed bulk scheme enhances the PMIPv6 performance by reducing the total handoff latency.